2017
DOI: 10.1186/s12916-017-0786-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and breast cancer risk by hormone receptor subtype: a nested case-control study in the EPIC cohort

Abstract: BackgroundCirculating osteoprotegerin (OPG), a member of the receptor activator of nuclear factor kappa-B (RANK) axis, may influence breast cancer risk via its role as the decoy receptor for both the RANK ligand (RANKL) and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Circulating OPG and breast cancer risk has been examined in only one prior study.MethodsA case-control study was nested in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. A total of 2008 inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 68 publications
6
34
3
Order By: Relevance
“…In prostate cancer, increased levels of OPG have been observed in patients with advanced cancer (33,34). In breast cancer, higher concentrations of OPG were associated with an increased risk of ER-negative breast cancer (35). In addition, preclinical studies indicate that OPG mediates tumor-promoting effects as a mediator of inflammation in breast cancer (36) and promotes metastases in triple-negative breast cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, increased levels of OPG have been observed in patients with advanced cancer (33,34). In breast cancer, higher concentrations of OPG were associated with an increased risk of ER-negative breast cancer (35). In addition, preclinical studies indicate that OPG mediates tumor-promoting effects as a mediator of inflammation in breast cancer (36) and promotes metastases in triple-negative breast cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…RANKL signaling also activates downstream signaling cascades such as NF-kB and cyclin D1 [ 6 , 12 ], which are key pathways, involved in breast cancer development [ 6 , 12 ]. Very recent studies conducted in Europe demonstrated that elevated serum RANKL levels are associated with increased breast cancer risk among women with high progesterone levels [ 24 ], while another study reported that elevated OPG levels are associated with increased breast cancer risk [ 25 ]. Our study adds to findings from these initial studies indicating that the RANK pathway plays an important role in breast cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…There was a modest reduction in risk (0.84) of ER+ breast cancer with high OPG (T1-342, T2-297, T3-290 cases). When comparing these data with Vik et al it appears that the range of OPG values are much lower in the Fortner et al study (17,18). The Vik et al study.…”
Section: Opg Protein Serum Levels and Breast Cancer Riskmentioning
confidence: 61%
“…OPG expression vs. breast cancer risk has been analyzed in a more recent, similar type of study (18). The European Prospective Investigation into Cancer and Nutrition (EPIC) cohort was a study designed to identify risk factors for cancer.…”
Section: Opg Protein Serum Levels and Breast Cancer Riskmentioning
confidence: 99%